2017
DOI: 10.1109/tbme.2017.2691399
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of Vocal Fold Dehydration During Phonation

Abstract: While vocal fold dehydration is often considered an important factor contributing to vocal fatigue, it still remains unclear whether vocal fold vibration alone is able to induce severe dehydration that has noticeably effect on phonation and perceived vocal effort. A three-dimensional model was developed to investigate vocal fold systemic dehydration and surface dehydration during phonation. Based on the linear poroelastic theory, the model considered water resupply from blood vessels through the lateral bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In vivo imaging accounts for homeostatic mechanisms that regulate water content and is a more accurate representation of vocal fold hydration. Wu and Zhang used a computational model to link increased dehydration with increased vibration amplitude, increased epithelial permeability, and reduced water resupply, but there were simplifications and assumptions made within that study as acknowledged by the authors 25 . Hanson et al used a tissue dehydration method of ex vivo systemic dehydration with a vacuum oven to simulate dehydration of the tissue beyond the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo imaging accounts for homeostatic mechanisms that regulate water content and is a more accurate representation of vocal fold hydration. Wu and Zhang used a computational model to link increased dehydration with increased vibration amplitude, increased epithelial permeability, and reduced water resupply, but there were simplifications and assumptions made within that study as acknowledged by the authors 25 . Hanson et al used a tissue dehydration method of ex vivo systemic dehydration with a vacuum oven to simulate dehydration of the tissue beyond the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…It was commonly observed that mucus is usually aggregated on the superior edge in vocally normal speakers. 44 Moreover, by using a poroelastic model, Wu and Zhang 23 also found that an upward movement of water within the surface liquid layer along the medial surface results in a gradual water accumulation on the superior edge of the vocal fold. The phenomenon revealed by our model is consistent with clinical observations and other model predictions.…”
Section: B Temporal Pattern Of the Fluid Movement In A Vibrating Vocal Foldmentioning
confidence: 97%
“…An interesting finding is that a global minimum in the total contact stress corresponds to physiologically reasonable tissue elasticity and fluid damping. Furthermore, Wu and Zhang 23 proposed a three-dimensional (3D) poroelastic model, considering water resupply, water movement within the tissue, water exchange through the epithelium, and surface fluid accumulation and discharge. They revealed that the dehydration generally increased with vibration amplitude, epithelial permeability, and reduced water resupply; moreover, the distribution of water loss within the vocal folds was non-uniform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry mouth syndrome can result from some pathophysiological conditions, like exposure to acute and chronic stress, eating disorders (such as anorexia nervosa), metabolic syndrome(s), Sjögren's and Sicca syndromes, and head/neck radiotherapy application. In turn, hyposalivation may predispose individuals to chronic oral pain, dental caries, taste changes, halitosis, voice and digestive disorders, and burning mouth syndrome [11,98]. Xerostomia may impact tissue viscosity of the vocal tract and oral mucosa and subsequently influence vocal function [12].…”
Section: Dry Mouth Syndrome and Body Dehydration Are Relevant For Botmentioning
confidence: 99%